Bbsmf1, an Nramp Family Transporter, Sustains Iron Homeostasis Through Cross Pathway Compensation in Beauveria bassiana - Mei Liu; Dan Ye; Guang Xia; Wenhui Yin; Shenghua Ying; Mingguang Feng; Jinli Ding; Min Lu (Current Microbiology, 2026)

Rhizosphere microbiome drives selenium bioavailability: Mechanisms and implications for biofortification - Lin Wu; Panpan Han; Huimin Lu; Wensheng Zhang (Applied Soil Ecology, 2026)

Effects of Intercropping Duration On Soil Ecosystem under Phoebe zhennan in Pinus massoniana Plantations in Yongchuan, Chongqing - Ximeng Yang; Min Lu; Feiyi Huang; Huadong Luo; Yuansong Guo; Jianping Luo; Chenggong Lei; Xueping Hu; Hengxing Zhu; Benwen Chen; Qianli Dai (Plant and Soil, 2026)

Temperature and salinity determine soil microbial carbon use efficiency in Phragmites australis marshes across five estuaries in China - Fengjiao Zhang; Na Liu; Min Luo; Pengfei Zhan; Kam W. Tang; Chuan Tong (Applied Soil Ecology, 2026)

Ecological engineering in pond aquaculture: a review from the whole‐process perspective in China - XingGuo Liu; Zhengyi Shao; Guofeng Cheng; Shimin Lu; Zhaojun Gu; Hao Zhu; Hongye Shen; Jie Wang; Xiaolong Chen (Reviews in Aquaculture, 2021)
Pond aquaculture undeniably offers the potential for food production worldwide. In China, 45.83% of aquatic production is currently from pond aquaculture. However, with the continuous expansion of this practice, environmental problems such as a high level of water consumption, aquaculture water deterioration, pollution from effluent and aquatic product quality decline seriously restrict the sustainable development of pond aquaculture. In this review, we summarise the (i) the impacts of pond aquaculture on the environment, (ii) research progress in pond aquaculture ecological engineering, (iii) existing technologies regarding pond aquaculture ecological engineering systems, (iv) effects of applying pond aquaculture ecological engineering and (v) summary and prospects. Moreover, we discuss the merits and drawbacks of each method and technology, and future research priorities are reviewed. With this, an understanding of the role played by ecological engineering in pond aquaculture is provided, as well as guidance for precisely managing aquaculture water and effluent, aquaculture practices, and technological developments. In summary, the pond aquaculture ecological engineering can be managed so as to improve animal welfare and the stability of water treatment systems, reducing the adverse effects on the environment and public health, and enabling the sustainable development of pond aquaculture.